Safety and efficacy of roux-en-y gastric bypass in older aged patients - JORGE HUMBERTO RODRIGUEZ QUINTERO; RACHEL GROSSER; GUSTAVO ROMERO VELEZ; VICENTE OMAR RAMOS-SANTILLAN; XAVIER PEREIRA; FERNANDO MUÑOZ FLORES; JENNY CHOI; ERIN MORAN-ATKIN; DIEGO CAMACHO; DIEGO LAURENTINO LIMA (Revista do Colégio Brasileiro de Cirurgiões, 2022)
ABSTRACT Introduction: laparoscopic Roux-en-Y Gastric Bypass (LRYGB) has been a revolutionary intervention for weight loss with reduction of up to 60-70% of excess body weight. However, these outcomes are not as well validated at the extremes of age, where the safety of the intervention still has some caveats. The aim of this study is to assess the efficacy and safety of primary LRYGB among different age groups. Methods: the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) database was queried for patients who underwent primary LRYGB from January 2014 to December 2017 at a single institution. Four groups were created and compared by dividing our sample by age quartiles. The primary outcome was percent excess weight loss (%EWL) at 1 year. Additional operative outcomes and complications were also compared across groups. Results: a total of 1013 patients underwent non-revisional LRYGB during the study period. Mean %EWL at one year was 55%. When compared between quartiles, there was a statistically significant difference in %EWL: 1st 62%, 2nd 57%, 3rd 54% and 4th 47% (p=0.010). The differences in the secondary outcomes between age groups did not demonstrate statistical significance. Conclusions: though patients in the fourth age quartile (range) did not demonstrate a statistically significant increase in adverse outcomes, they did lose less weight compared to other cohorts. The %EWL at one year after RYGB varied by age in our cohort. Goals after bariatric surgery should be individualized as weight loss is less robust with aging.